Galdan boshigt and the Russian ambassador: meeting, mistrust - S. Chuluun (Nomadic Civilization: Historical Research, 2022)
The history of Galdan Boshigt of Oirat is one of the most important studies in Mongolian-Russian relations in the 17th century. The history of Galdan Boshigt’s relationship can be traced back to his reign in the Dzungarian Empire. Galdan Boshigt’s foreign policy and operations should focus on relations with Dzungaria, Central and East Asia, and the Manchu Dynasty. However, a number of Chinese and Russian scholars have studied the issue. Therefore, I did not touch on the issue of Galdan Boshigt’s relations, and The author tried to focus on how he interacted with Russia, the specifics of his relations, the historical situation at that time.